스포츠센터 이용고객이 인식하는 서비스스케이프가 고객만족, 고객신뢰 및 재등록의도와의 관계 - 김순희(Soon-Hee Kim) (한국콘텐츠학회 논문지, 14(10), 2014)
The purpose of this study was to find out the relation between servicescape recognized by sports center and customer satisfaction, customer trust and customer's intention to reenroll. For the subject of this study, we selected 363 persons among customers who used 5 sports centers located at 'B' Metropolitan city & 'K' do (prefecture) through the Convenient Sampling Method. For the analysis, we used SPSS 18.0 Statistics Package as a research tool and have carried out Factor Analysis, Reliability Analysis, Co-relation Analysis, Frequency Analysis, and Regression Analysis. The results were as follows: First, the servicescape has a positive effect on the customer satisfaction. Second, the customer satisfaction has a positive effect on the customer trust. Third, the customer satisfaction has a positive effect on the customer's intention to re-enroll. Fourth, the customer trust has a positive effect on the customer's intention to reenroll. 본 연구는 스포츠센터 이용고객들이 인식하는 서비스스케이프가 고객만족, 고객신뢰, 재등록의도와의 관계를 규명하는데 목적이 있다. 연구대상은 K도, B광역시에 소재하고 있는 스포츠센터 5곳의 이용고객을 모집단으로 선정하였으며, 편의표본추출법을 사용하여 총 363명을 유효 표본으로 선정하여 본 연구의 자료로 이용하였다. 조사도구는 SPSS 18.0 통계패키지를 이용하여 요인분석, 신뢰도분석, 상관관계분석, 빈도분석, 회귀분석을 이용하였으며, 결론은 다음과 같다. 첫째, 서비스스케이프는 고객만족에 긍정적인 영향을 미친 것으로 나타났다. 둘째, 고객만족은 고객신뢰에 긍정적인 영향을 미친 것으로 나타났다. 셋째, 고객만족은 재등록의도에 긍정적인 영향을 미친 것으로 나타났다. 넷째, 고객신뢰는 재등록의도에 긍정적인 영향을 미친 것으로 나타났다.